Post occupancy evaluation of the Faculty of Geoinformation And Real Estate, Block T06 UTM [electronic resource] - Izzah Shamsol Kahar, 1992-, author 636649; Izran Sarrazin Mohammad, 1975- supervisor 509206; Fakulti Geoinformasi dan Harta Tanah 555724 (2015)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2015